Stereocontrolled Total Syntheses of Optically Active Furofuran Lignans - Inai, Makoto; Ishikawa, Ryo; Yoshida, Naoto; Shirakawa, Nana; Akao, Yusuke; Kawabe, Yusuke; Asakawa, Tomohiro; Egi, Masahiro; Hamashima, Yoshitaka; Kan, Toshiyuki (Synthesis, 2015)
Plant products (+)-sesamin, (+)-sesaminol, (+)-methylpiperitol, (+)-aschantin, and (+)-5'-hydroxymethylpiperitol were synthesized in a highly stereocontrolled manner through l-proline-catalyzed bifunctional-urea-accelerated cross-aldol reaction, followed by biomimetic construction of the furofuran lignan skeleton through a quinomethide intermediate.
Keywords: aldol reaction; natural products; organocatalysts; proline; stereoselective synthesis